3D Printed Organ Models with Physical Properties of Tissue and Integrated Sensors. Issue 3 (6th December 2017) - Qiu, Kaiyan; Zhao, Zichen; Haghiashtiani, Ghazaleh; Guo, Shuang‐Zhuang; He, Mingyu; Su, Ruitao; Zhu, Zhijie; Bhuiyan, Didarul B.; Murugan, Paari; Meng, Fanben; Park, Sung Hyun; Chu, Chih‐Chang; et al.
Abstract: The design and development of novel methodologies and customized materials to fabricate patient‐specific 3D printed organ models with integrated sensing capabilities can yield advances in smart surgical aids for preoperative planning and rehearsal. Here, 3D printed prostate models are demonstrated with physical properties of tissue and integrated soft electronic sensors using custom‐formulated polymeric inks. The models show high quantitative fidelity in static and dynamic mechanical properties, optical characteristics, and anatomical geometries to patient tissues and organs. The models offer tissue‐mimicking tactile sensation and behavior and thus can be used for the prediction of organ physical behavior under deformation. The prediction results show good agreement with values obtained from simulations. The models also allow the application of surgical and diagnostic tools to their surface and inner channels. Finally, via the conformal integration of 3D printed soft electronic sensors, pressure applied to the models with surgical tools can be quantitatively measured. Abstract : A patient‐specific 3D printed organ model, fabricated via customized polymeric inks, exhibits physical properties of tissue and integrated sensing capabilities and can be applied for organ physical behavior prediction and quantitative surgical rehearsal. The concept of creating 3D printed organ models with physical properties of tissue, anatomical fidelity, and integrated 3D printed electronics suggests a new paradigm for surgical rehearsal.